Germany and the Seventeenth-Century Crisis - Ogilvie, Sheilagh C. (The historical journal, 1992)
This article surveys the debate on the ‘General Crisis’ of the seventeenth century in the light of hitherto neglected research. Firstly, most theories of the crisis fail to combine its economic and socio-political aspects. Secondly, few explanations of the crisis take account of evidence from the local and regional levels. Thirdly and most seriously, theories of the crisis have ignored Germany, while historians of Germany have ignored the crisis debate. This article seeks to fill these gaps. It puts Germany at the centre of a comprehensive theory of the crisis that takes existing crisis theories as its starting point, but also shows how the Thirty Years War, largely caused by the peculiar institutional structure of the Holy Roman Empire, in turn wrought significant institutional change, not just in Germany, but throughout Europe.